Patients with SATB2‐associated syndrome exhibiting multiple odontomas. Issue 12 (21st December 2018) - Kikuiri, Takashi; Mishima, Hiroyuki; Imura, Hideto; Suzuki, Satoshi; Matsuzawa, Yusuke; Nakamura, Takashi; Fukumoto, Satoshi; Yoshimura, Yoshitaka; Watanabe, Satoshi; Kinoshita, Akira; Yamada, Takahiro; Shindoh, Masanobu; et al.
Abstract: Special AT‐rich sequence‐binding protein 2 ( SATB2 )‐associated syndrome (SAS) is characterized by alterations of SATB2. Its clinical features include intellectual disability and craniofacial abnormalities, such as cleft palate, dysmorphic features, and dental abnormalities. Here, we describe three previously undiagnosed, unrelated patients with SAS who exhibited dental abnormalities, including multiple odontomas. Although isolated odontomas are common, multiple odontomas are rare. Individuals in families 1 and 3 underwent whole‐exome sequencing. Patient 2 and parents underwent targeted amplicon sequencing. On the basis of the hg19/GRCh37 reference and the RefSeq mRNA NM_001172517, respective heterozygous mutations were found and validated in Patients 1, 2, and 3: a splice‐site mutation (chr2:g.200137396C > T, c.1741‐1G > A), a nonsense mutation (chr2:g.200213750G > A, c.847C > T, p.R283*), and a frame‐shift mutations (chr2:g.200188589_200188590del, c.1478_1479del, p.Q493Rfs*19). All mutations occurred de novo. The mutations in Patients 1 and 3 were novel; the mutation in Patient 2 has been described previously. Tooth mesenchymal cells derived from Patient 2 showed diminished SATB2 expression. Multiple odontomas were evident in the patients in this report; however, this has not been recognized previously as a SAS‐associated phenotype. We propose that multiple odontomas be considered as an occasional manifestation of SAS.